PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN - Supar, Dewa Ayu Wina Ariyunita; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
This study aims to clarify the effect of customer relationship management and customer satisfaction to customer loyalty Ramayana Department Store in Denpasar. The study uses a quantitative approach. The sample in this study of 120 people by using non-probability sampling and purposive technique. The research instrument a questionnaire and analyzed using path analysis (path analysis). The results of this study indicate that the customer relationship management and customer satisfaction have partial significant influence on customer loyalty where customer satisfaction also has a positive role in mediating the effect of CRM on customer loyalty. Customer relationship management and customer satisfaction affects customer loyalty at 73.5 percent while the remaining 26.5 percent is influenced by other factors.
Keywords: customer relationship management (CRM); satisfaction; customer loyalty